Calcified mitro-aortic continuity and mitral regurgitation in patients undergoing transcatheter aortic valve replacement. (25th November 2020) - Rys, M; Szymanski, P; Zatorska, K; Michalowska, I; Witkowski, A; Hryniewiecki, T
Abstract: Introduction: Calcified aortic stenosis (AS) and mitral annular calcification (MAC) have similar etiology and pathophysiological mechanisms. Half of all patients undergoing transcatheter aortic valve implantation (TAVI) have MAC. Several studies assessed the role of mitral regurgitation (MR) following TAVI but only few examined influence of MAC on its changes after TAVI. MAC frequently coexists with the calcification of mitro-aortic continuity (CMAC). Purpose: Presence of CMAC may influence the results of TAVI, especially in the case of deeper implantation, protruding to let ventricular outflow tract (LVOT). In the present study we aimed at qualitative and semi-quantitative analysis of calcifications of the mitral complex – MAC and CMAC in multi-slice computed tomography (MSCT) in patients qualified to TAVI, in order to assess their impact on the occurrence and dynamics of MR following aortic valve implantation. Methods: MAC was assessed quantitatively (Calcium Score) and semi-quantitative scale in depending on the degree of annular involvement. CMAC was evaluated in semi-quantitatively scale in depending on length of calcifications in the largest dimension. Subsequently patients were classified in a dichotomous manner as having non-severe or severe MAC and CMAC. All patients underwent transthoracic echocardiographic examinations prior to the procedure and after TAVI. Changes of MR severity following TAVI were defined as no change, improvement or worsening by at least one degree. Results: The study group consisted of 94 patients. Fifty six (59.6%) out of 94 patients had MAC and 21 patients (22.3%) had severe MAC. Patients with MAC had higher mean aortic gradients (54.07±13, 62 mmHg vs 46.79±14.42 mmHg, p=0.02) and smaller left ventricular diastolic diameter (46.09±6.86 mm vs 51.19±8.42 mm, p=0.002). Almost half of the patients - 46 (48.9%) had CMAC and 12 patients (12.8%) had severe CMAC. Patients with CMAC had higher Calcium Score Aortic Valve (3773.67±1734.02 Hounsfield Units (HU) vs 2875.1±1352.76 HU, p=0.006) and smaller AVA (0.59±0.16 cm 2 vs 0.66±0.20 cm 2, p=0.052). Before TAVI 35.1% of patients had more than mild MR. MR improved by at least one grade following TAVI in 17 (18.1%) patients and worsened by at least one grade in 7 (7.5%) patients. In multivariable logistic regression analysis MR worsening was associated with higher CMAC [OR 1.092, 95% CI: 1.006–1.185, p=0.035]. Conclusions: The study demonstrated CMAC is prevalent in patients undergoing TAVI. CMAC was associated with MR worsening. This is a novel finding, which may be particular importance in patients with severe AS and coexisting MR in whom arguments for and against surgical repair of concomitant mitral insufficiency are considered, as opposed to isolated aortic valve procedure. Funding Acknowledgement: Type of funding source: None